Clearing the Prophet’s Ijtihād from error - al-Dalati, Abdulhadi Mohammad (Journal of Islamic Sciences, 2021)
There is no doubt that the Prophetic traditions (sunnah) are amongst the foundations upon which Muslims base their Islamic beliefs. They are also one of the pillars that high-ranking scholars rely upon in order to derive religious maxims/rules. In this era, many misconceptions surfaced in regards to the credibility of the Prophetic Sunnah. Through these misunderstandings, numerous people have attempted to prevent others from being committed to the Sunnah and implementing its noble teachings. Perhaps, also, some contemporaries might have referred to certain claims, in some books, which indicate to the possibility of error in the Ijtihād of the Prophet regarding religious matters. This has consequently resulted in repelling people from committing to the Prophetic traditions. Based upon this, through my research, I will attempt to investigate in this matter so as to clarify that the reality is contrary to their claims. Instead, the Prophet, ṣalla-Allāhu ʿalayhi wa-sallam, is impeccable and protected from erring when performing Ijtihād as he is protected from making mistakes in regards to what he relates from His Lord through revelation. I have collated many supportive evidences as well as making note of the misrepresentations I have found and responded to them. Amongst the conclusions this research has arrived at is that when Jesus descends from the sky, all disagreements pertaining to judicial schools of thought will cease, because his Ijtihād is protected from error, therefore his religious opinion would be the accepted one. The methodologies I adopted herein are descriptive & analytical. I hope that this research becomes a new addition to the Islamic body of research and an aid to researchers. I also hope for this research project to fill the gap in extant research, as I have not found anyone who has delved into this matter as I have.